Mu-opioid receptor expression on B cells as a potential biomarker for chronic pain: a follow-up study with patients with fibromyalgia - Valentina Malafoglia; William Raffaeli; Sara Ilari; Chiara Gioia; Cristina Iannuccelli; Michael Tenti; Laura Vitiello; Stefania Proietti; Leonardo Lupacchini; Lucia Carmela Passacatini; Carlo Tomino; Mollace Vincenzo; et al. (PAIN Reports)
Abstract. Introduction:. Before COVID-19 pandemic, we identified the percentage of B cells expressing the Mu-opioid receptor (Mu+ B cells) as a potential marker, named Mu-Lympho-Marker (MLM), for chronic pain (CP) in patients with fibromyalgia (FM) and osteoarthritis. Objectives:. Here, we demonstrate the stability of MLM over time through a comparative analysis of biological, clinical, and psychological data collected from a subgroup of patients with FM across 2 distinct research periods. Methods:. This is an observational, longitudinal study. Fibromyalgia participants enrolled in the first study were called back for follow-up sampling. Clinical data were recorded. Pain score was reported using the Numerical Rating Scale. Mu+ B cells percentage of expression was analyzed by flow cytometry. Immunofluorescence analyses were performed to explore the cellular localization of Mu-opioid receptor. Pain-free subjects served as control group. All the participants filled out self-reported psychological tests. Data were statistically analyzed. Results:. Mu+ B cells percentage of expression was constant in patients with FM, who consistently showed lower values than control group after 2 years (difference in the mean: 32.0 ± 4.4, t = 7.330, IC 95% [23.2–40.9], P < 0.0001). Confocal microscopy analyses revealed Mu cytoplasmic localization in patients with FM. We observed no significant changes between psychological outcomes during the 2 phases of the study, nor did we find any correlations with biological findings. Conclusion:. Mu-Lympho-Marker could be a promising marker for CP, as seen in FM cohort, and could be helpful for accurate diagnosis and tailored rehabilitation strategies. Further studies are needed to study MLM in CP of different aetiologies.